The tax planning and its effect on the investment: On sample of Iraqi Contribution Company (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The importance of the current study  lies in the  importance of the  Tax policy that  being considered one of the most important tools working on fulfilling  the  social,  financial  and economic  goals  and improving  the investment environment  in the country  to become  having the ability to  activate the  national economy. The current study  has  referred  that  (  Has  the  tax planning  practiced by  the Iraqi  contribution  companies  led to increase  the  far-term tax  outcome through  getting  benefit of   the monetary  funds  and expansion in  the economic  activities  or establishing  new economic  structures  and consequently  led  to increase   the tax? The hypothesis of the current study  has indicated that the  tax planning  practiced by the  Iraqi contribution   contribute  into  encouraging  the  investment  and new projects .  The research aims toexplain the concept of the tax planning   and its strategicimportance, and to what   extent   it depicts policies of expansion in investment.  The research has concluded  set of conclusions  , most importantly,  the Iraqi  companies   have agreed that  the tax  availability that could be obtained  through  the tax planning   has been considered   a factor  for attracting  the  investment  through  paying attention to  the nature of  the monetary  availabilities. As a result, the investment  is considered  as a main factor  in defying  the  state's  economic center  in the short-term an the main reason of the economic growth  lies in  creating  jobs opportunities  and production increase , technology   development and  exports expansion . Along withthe currencies ' entry. Thus, all these factors reflect positively on the companies ' contribution into the economy growth and taxplanning increase.  Most important recommendations  lie in the contribution of Iraqi companies  to pay attention on  the tax planning  for  reducing  the tax regulations  based on laws  and achieving   more  profits   and monetary availability to be used  in  fields of expansion  and to open  specialized companies  or   branches  in and outside the country  as to secure  its work  continuation and competition.